Nutritional Approaches of University Students During the COVID-19 Pandemic - Karakoç, Önder (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate nutritional approaches in university students during the COVID-19 pandemic. Methods: A total of 579 university students (male: 296, female: 283) participated in the study. Besides the personal form, the students filled out a nutrition approach testing questionnaire. Students participated voluntarily. The surveys were conducted on social media. Independent sample t and one-way analysis of variance (ANOVA) were applied to analyze the difference in groups. Results: Nutrition scores on the days of curfew (Lockdown) and the days when there is no prohibition or restriction did not change according to gender (p>0.05). A significant difference was found in the nutrition scores of the students according to the levels they felt on the days when there was a curfew and, on the days, when there was no prohibition or restriction (p